Peningkatan Kualitas dan Pemanfaatan Limbah Hasil Pembuatan VCO (Virgin Coconut Oil) IKM Rumah Ikhtiar - Rosdiani Azis; Ikrima Staddal; Syahmidarni Al Islamiyah (LPPM Universitas Trunojoyo Madura, 2021)
Posso Village is one of the villages located in Kwandang District, through a village-owned enterprise formed a successful IKM together that produces traditional coconut oil. The purpose of this service activity is to improve the quality of traditional coconut oil and its waste and the management of partner businesses. The results of this service activity obtained several machines such as a coconut peeler machine with an average coconut peeling of about 18 s/piece at a machine speed of 2000 rpm and a shaft 25 rpm, a large capacity coconut milk squeezer machine with manual operation via hydraulic power, a VCO mixer machine with a capacity of 20 liters with a rotational speed of 900 rpm to 4200 rpm, an ethanol distillation machine with a capacity of 30 liters equipped with a condenser, a drum for burning shells into charcoal, product packaging and label designs, online trading accounts and operations have been obtained by partners.